Pengaruh Model Problem-based Learning terhadap Kemampuan Pemecahan Masalah Matematis Siswa - Detya Eka Nurwanty Putri; Maulana Maulana; Riana Irawati (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
The problem of low mathematical problem solving ability of students that occurs in the field can be overcome by choosing the right learning model as an effort that can be made to improve problem solving ability. Problem-based learning model is a relevant learning model to improve problem solving ability. This study aims to determine the difference in the effect of problem-based learning model and conventional learning on students' mathematical problem solving ability. This research used experimental method with nonequivalent control group design. The study population was fourth grade students of A accredited elementary schools in Cimalaka Subdistrict with samples of fourth grade students of SDN Margamukti as the experimental class and fourth grade students of SDN Licin as the control class. The instrument in the form of a description test was used to measure mathematical problem solving ability. The results showed that the application of the problem-based learning model had a significant effect. The results of the average pretest score of 45 became 82 on the posttest and the average gain value was 0.63. While conventional learning obtained an average pretest score of 52 to 76 on the posttest with an average gain value of 0.46 so that the problem-based learning model is more effective than conventional learning, as evidenced by the higher average gain value of problem-based learning.